Nutritional status of mother-child pairs and factors associated with double burden of malnutrition among Orang Asli (Temuan) households in Selangor, Malaysia - Ismail, Rozalina (2020)
Poverty, urbanization, and nutrition transition are identified as factors associated with double burden of malnutrition (DBM). However, there are other underlying factors associated with DBM at the household level. This cross-sectional study aimed to determine the nutritional status of mother-child pairs and factors associated with DBM among Orang Asli (Temuan) households in Selangor. Non-probability sampling was used in this study. A total of 451 mother (20 – 49 years) and child (6 – 59.9 months old) pairs participated in this study. Information on demographic and socio-economic status and dietary intake of mothers and children were obtained using a pre-tested questionnaire while food security status was assessed using Radimer Cornell/ Hunger and Food Security Instrument. Anthropometric measurements of mothers and children were taken using standard procedures. DBM household was defined as the coexistence of an overweight/obese mother and an underweight/stunted child (OWOBM/ UWSTC) within the same household. Majority (79.2%) of the households were living below the poverty line for Peninsular Malaysia of RM 240.00. Mean age of mothers and children were 29.51 ± 6.59 years and 27.67 ± 15.40 months, respectively. About 90% of the households experienced some forms of food insecurity, namely household food insecure (29.9%), individual food insecure (21.1%) and child hunger (38.8%). Overweight and obesity among the OA mothers were 28.2% and 35.0%, respectively. About 23% of the OA children were underweight, and 35.7% were stunted. About 29% of the households were DBM, while 23.3% of mother-child pairs were in the Normal households. The average daily energy intake of mothers was 1,510 kcal. Although 54.1% of mothers met the RNI (2017) for energy intake, RNI attainment was poor for micronutrients such as vitamin A, thiamine, riboflavin, vitamin C, calcium, iron, and folate. Mothers also had inadequate serving intakes for most of food groups, except grains and cereals. Majority of children had inadequate intake of energy, micronutrients (vitamin A, calcium and folate) and number of servings for fruits, vegetables, legumes, meat, fish, and milk and dairy products. This study revealed that food insecure (AOR: 3.64; 95% CI: 1.08–12.29), children aged ≥ 24 months (AOR: 4.44; 95% CI: 2.38–8.29), mothers with height < 150 cm (AOR: 2.21; 95% CI: 1.22–3.98), mothers who had energy intake ≥ RNI (AOR: 3.85; 95% CI: 1.38 – 10.81), and children who did not meet the recommended serving intake for vegetables (AOR: 6.82; 95% CI: 1.22 – 38.25) were significantly associated with DBM at the household level. Also, increased percentage of RNI for vitamin C among mothers was significantly less likely to be associated with DBM. DBM at the household level is a public health concern among OA households. Household, mother, and child factors were associated with DBM. Therefore, the strategies for DBM prevention in this vulnerable population should consider food or financial aid, promotion of healthy lifestyle, and appropriate infant and young child feeding practices.